Voltage security enhancement via coordinated control. - Qiang Wu
The problem of analytically coordinating dissimilar voltage control actions to prevent voltage collapse in a large power system is addressed. A framework for hybrid voltage control based on coordination of controls with different response time and dynamic characteristics is presented. The proposed method is based on a security constrained steady-state approach. The minimum distance from the operating point to the bifurcation boundary is used to evaluate system voltage security. The optimal control direction toward adequate security is then obtained by calculating the sensitivity of the minimum distance with respect to control parameters. The actual dispatch of controls along the optimal direction, which takes into account impacts of economic cost and control availability, is determined as the solution of a multiple-stage optimization problem using differential dynamic programming. The algorithm is demonstrated for a system with dynamic load models representing the main grid of New South Wales, Australia
Keywords: Australia; New South Wales; Bifurcation boundary; Control availability; Coordinated control; Differential dynamic programming; Dynamic characteristics; Dynamic load models; Economic cost; Hybrid voltage control; Multiple-stage optimization problem; Operating point; Optimal control direction; Response time; Security constrained steady-state approach; System voltage security evaluation; Voltage collapse prevention; Voltage security enhancement